Grain quality in superior and inferior grains of soft and non-soft rice varieties from the Yangtze River Delta - Chen, Xi; Cao, Jiale; Ma, Zhongtao; Yu, Jianghui; Zhu, Ying; Xu, Fangfu; Hu, Qun; Liu, Guodong; Li, Guangyan; Wei, Haiyan (Frontiers in Plant Science, 2025)
ObjectiveThis study aims to establish a scientific basis for improving rice quality by investigating the relationship between variations in eating and appearance quality and the starch and protein content in soft and non-soft rice varieties.MethodsTwo soft rice varieties, Nanjing 5718 and Nanjing 9108, were compared with two non-soft rice varieties, Huaidao 5 hao and Huajing 5 hao. The study focused on eating and appearance quality, starch and protein content, and how these factors varied between superior and inferior grains within each variety.ResultsCompared to non-soft rice, soft rice has some disadvantages in appearance quality, which is characterized by high chalky grain rate and chalkiness degree, and large differences in appearance between superior and inferior grains. This is mainly due to the low proportion of high grain weight grains, low amylose content, abnormal development of starch structure, and large protein bodies with high globulin and glutenin content, which destroys the close accumulation of starch particles, resulting in increased light scattering, increased chalkiness, and reduced transparency. Although the appearance quality of soft rice is not outstanding, its eating quality is extremely excellent, which is embodied in good appearance, high viscosity, good balance, high taste value and low hardness. This superior performance may be due to the high proportion of amylopectin in soft rice, which helps to improve the overall taste. In contrast, the amylose content of non-soft rice is higher, which leads to the increase of rice hardness and the decrease of viscosity. In addition, the gelatinization property of soft rice starch is more favorable, which makes the starch dissolve more in the cooking process, so as to further improve its eating quality.